System-Wide Expression and Function of Olfactory Receptors in Mammals - S. June Oh (Genomics & Informatics)
Olfactory receptors (ORs) in mammals are generally considered to function as chemosensors in the olfactory organs of animals. They are membrane proteins that traverse the cytoplasmic membrane seven times and work generally by coupling to heterotrimeric G protein. The OR is a G protein‒coupled receptor that binds the guanine nucleotide-binding Gαolf subunit and the Gβγ dimer to recognize a wide spectrum of organic compounds in accordance with its cognate ligand. Mammalian ORs were originally identified from the olfactory epithelium of rat. However, it has been recently reported that the expression of ORs is not limited to the olfactory organ. In recent decades, they have been found to be expressed in diverse organs or tissues and even tumors in mammals. In this review, the expression and expected function of olfactory receptors that exist throughout an organism’s system are discussed.